2019
DOI: 10.1007/s12630-019-01438-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of myocardial and kidney injury following endovascular aortic repair: a retrospective cohort study

Abstract: Purpose We performed a retrospective cohort study in patients who underwent endovascular aneurysm repair (EVAR) to determine the incidence and predictors of myocardial injury and acute kidney injury (AKI). Methods We included 267 consecutive patients who underwent EVAR at two tertiary centres in Canada and Poland. The primary outcome was myocardial injury during hospital stay after EVAR defined as a troponin elevation (ultra-sensitivity troponin I Vidas C 19 ngÁL-1 , non-high-sensitivity troponin I Vidas C 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 39 publications
4
12
2
Order By: Relevance
“…Whereas 62.2% of our patients developed tachyarrhythmia which increased oxygen consumption and, thus, myocardial oxygen delivery-consumption mismatch. In line with others [ 41 ], long duration of surgery was also identified as a risk factor of myocardial injury in this cohort. On the other hand, we identified male sex as a protective factor.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas 62.2% of our patients developed tachyarrhythmia which increased oxygen consumption and, thus, myocardial oxygen delivery-consumption mismatch. In line with others [ 41 ], long duration of surgery was also identified as a risk factor of myocardial injury in this cohort. On the other hand, we identified male sex as a protective factor.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to our study, previous studies have mainly focussed on individual complications after EVAR, mostly myocardial injury [5][6][7]. To our knowledge no other studies have investigated MACE after EVAR within the range of our definition.…”
Section: Discussionmentioning
confidence: 86%
“…Identifying predictive factors for cardiac events could be especially helpful to anticipate problems that may occur after EVAR. A few studies investigated multiple predictors for myocardial injury after EVAR, where the only shared predictor was an increasing age [5][6][7] . The occurrence of myocardial injury, comparable with other studies [5][6][7] , was also found to be significantly different between patients aged above and below 75 years in a study, that mainly focussed on the effect of single risk factors, like other studies [8][9][10][11][12][13][14] , on survival after aneurysm repair 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations